ANALYSIS OF THE INTERNACIONAL LICENCIATE DEGREE PROGRAM IN THE CONTEXT OF THE HIGHER EDUCATION INTERNATIONALIZATION - Souza, Nayara Christine (2016)
The objective of this study is to describe and analyze aspects of Brazilian higher education internationalization in the context of globalization and its specific relationship with the policy implemented in the period 2010-2012 by the International Licentiate Degree Program (PLI in Portuguese acronym), officially established in 2010 by CAPES. Thereunto, quantitative and qualitative analysis was carried out, based on documentary and bibliographic research. In theory, the own Higher Education Institutions internally assess the impact of the experience of students in their professional training. However, the assessment criteria of the process are not covered by the notices published by CAPES, leaving open and ambiguous the expected results, in addition to the quantity of teachers and students involved.